PENERAPAN PASAL 362 KUHP DALAM KASUS PENCURIAN RINGAN DAN TANTANGANNYA DITINGKAT HUKUM - Nur Sandi (LPPM institut Teknologi Bisnis AAS Indonesia, 2025)
Theft is one of the most common crimes in society. Article 362 of the Criminal Code (KUHP) generally regulates the crime of theft, which carries a maximum penalty of five years' imprisonment or a fine. In law enforcement practice, not all thefts have significant consequences, as there are also thefts with small losses, often referred to as petty theft. The handling of petty theft cases often generates debate, particularly regarding the sense of justice, proportionality of punishment, and the effectiveness of law enforcement. This study aims to analyze the application of Article 362 of the Criminal Code in petty theft cases and examine the various challenges faced by law enforcement officials in practice. The research method used is normative legal research with a statutory and conceptual approach. The results indicate that the application of Article 362 of the Criminal Code to petty theft still faces legal and sociological obstacles, particularly regarding the interpretation of the elements of the offense, the application of the principle of justice, and the need for criminal law reform. Keywords: Article 362 of the Criminal Code, petty theft, law enforcement, justice.